Application of a copper-manganese spinel catalyst in anaerobic dehydrogenation of ethanol to acetaldehyde

The preparation of copper manganese spinel catalyst by the freezing-assisted sol gel method solved the problem of low mass spacespeed of ethanol dehydrogenation catalyst, and achieved high catalytic activity and high product space-time yield at high quality spacespeed.

CN118976511BActive Publication Date: 2025-04-11NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411143968.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-04-11
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The existing ethanol dehydrogenation catalysts have the problem of low mass space velocity in the preparation of acetaldehyde and hydrogen, which affects the catalytic activity and product space-time yield.

Method used

The copper-manganese spinel catalyst is prepared by the freezing-assisted sol-gel method. By regulating the copper-manganese ratio and calcining conditions, the mass spacespeed and catalytic activity of the catalyst are improved.

Benefits of technology

Under normal pressure conditions, the mass space velocity of the copper manganese spinel catalyst reached 31.72h-1, the ethanol conversion rate can reach 84.3%, and the acetaldehyde selectivity reaches 95%, while improving the product space-time yield and atomic utilization rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118976511B_ABST
    Figure CN118976511B_ABST
Patent Text Reader

Abstract

The present invention discloses the application of a copper-manganese spinel catalyst in the dehydrogenation of ethanol to prepare acetaldehyde, and belongs to the technical field of multiphase catalysis for the dehydrogenation of ethanol to prepare acetaldehyde and hydrogen, and specifically relates to the preparation of a series of copper-manganese spinel catalysts and their applications. The catalyst of the present invention is applied to the reaction of ethanol to prepare acetaldehyde and hydrogen without oxygen by dehydrogenation. The reaction is carried out in a fixed bed reactor, the reaction atmosphere is nitrogen, the reaction temperature is 160-280°C, and the acetaldehyde selectivity is about 95%, achieving high selectivity for the preparation of acetaldehyde and hydrogen under relatively mild conditions. The system has the significant advantages of simple catalyst preparation, high catalytic activity under high mass space velocity conditions, high acetaldehyde time-space yield, high system atomic utilization, and good stability. The copper-manganese spinel catalyst in the system has a mass space velocity of 31.72h ‑1 It is higher than the reported value, which solves the problem of low catalyst mass space velocity in the reaction system of ethanol dehydrogenation to prepare acetaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of spinel catalytic materials and heterogeneous catalysis in anaerobic dehydrogenation, and in particular to preparing acetaldehyde and hydrogen through an anaerobic dehydrogenation process using ethanol as a reactant and spinel as a heterogeneous catalyst. Background Art

[0002] With the depletion of fossil fuels and the intensification of environmental pollution, actively researching and developing alternative energy sources is a more important issue at present. In recent years, due to the advantages of biomass ethanol such as large annual output, wide distribution, renewable, and environmentally friendly, it is extremely necessary to utilize it in a high-value-added manner. At present, ethanol can be converted into high-value-added products such as butanol and 1,3-butadiene. Among them, ethanol dehydrogenation is a key step in ethanol conversion, and its in-depth research has opened up a channel for ethanol to be converted into high-value-added products. In addition, acetaldehyde itself, as an extremely important organic synthesis intermediate, can be converted into chemical products such as acetic acid, ethyl acetate, peracetic acid, pentaerythritol, etc., and has a high application value.

[0003] At present, there are three methods for preparing acetaldehyde: ethylene oxidation, acetylene hydration, and ethanol oxidation. The first two have certain applications in industry, but their raw materials rely on fossil energy, and they have certain hazards to equipment and the environment, and the catalyst cost is relatively high. Compared with them, the ethanol oxidation method is more excellent, and the ethanol oxidation method is divided into ethanol oxidative dehydrogenation and ethanol direct dehydrogenation.

[0004] In the study of ethanol dehydrogenation, most catalysts still have problems such as poor stability and low processing capacity. For example, Chinese patent application CN 110385139 A loaded Cu on a boron-containing compound and achieved a mass space velocity of 9.468 h at 240 ° C and atmospheric pressure. -1 , ethanol conversion rate 43.3%, acetaldehyde selectivity 95.4%. Chinese patent application CN 110479337 A loads the active component Co2C on reduced graphene oxide material, at 400℃, atmospheric pressure, the mass space velocity is 0.032h -1 , ethanol conversion rate 88.1%, acetaldehyde selectivity 99.1%. Chinese patent application CN 105148911 A Cu is loaded on carbon material, at 260 ° C, atmospheric pressure conditions, the mass space velocity is 2.37h -1 , ethanol conversion rate is 62.3%, and acetaldehyde selectivity is 93.4%.

[0005] The copper-manganese spinel catalyst prepared by the cryo-assisted sol-gel method of the present invention is heated to 280°C and atmospheric pressure at an ethanol flow rate of 4.02 mL·h -1 , mass airspeed is 28.83h -1, ethanol conversion rate can reach 84.3%, acetaldehyde selectivity 95%, acetaldehyde space-time yield 21.73h -1 , hydrogen space-time yield 20h -1 There have been certain breakthroughs in the field of anaerobic dehydrogenation of ethanol to produce acetaldehyde and hydrogen, and it has broad prospects in industrial applications. Summary of the invention

[0006] The purpose of the present invention is to explore the application of copper-manganese spinel catalyst in the field of dehydrogenation, and to improve the problem of low mass space velocity in the current process of ethanol dehydrogenation to acetaldehyde. The acetaldehyde preparation method has a simple reaction process, high selectivity of the catalyst for acetaldehyde, large ethanol processing capacity of the catalyst, simple preparation, and certain industrial application prospects. The mass space velocity of the copper-manganese spinel catalyst in the system is 31.72h -1 It is higher than the reported value, which solves the problem of low catalyst mass space velocity in the reaction system of ethanol dehydrogenation to prepare acetaldehyde, achieves high catalytic activity under high mass space velocity conditions, and also achieves the goals of high product space-time yield and high atomic utilization rate. It has broad prospects for industrial application.

[0007] In order to solve the technical problem of the present invention, the technical scheme proposed is: an application of a copper-manganese spinel catalyst in the dehydrogenation of ethanol to prepare acetaldehyde, and the process of dehydrogenation of ethanol to prepare acetaldehyde is as follows: using ethanol as a raw material and a multiphase copper-manganese spinel as a catalyst, reacting in a fixed bed reactor, reacting to prepare acetaldehyde and hydrogen at a temperature of 160 to 280° C. and normal pressure;

[0008] The multiphase copper-manganese spinel catalyst is composed of copper, manganese active metals and a chelating agent; the copper metal in the copper-manganese spinel catalyst is derived from copper nitrate trihydrate; the manganese metal in the copper-manganese spinel catalyst is derived from one of manganese acetate tetrahydrate and manganese nitrate tetrahydrate; the chelating agent is citric acid, and the molar ratio of copper to manganese metal is 2-1:1-2.

[0009] Preferably, the preparation method of the multiphase copper-manganese spinel catalyst is as follows: Cu(NO3)2.3H2O, Mn(CH3COO)2.4H2O and citric acid are co-dissolved in deionized water, stirred and mixed evenly, anhydrous ethanol is added dropwise thereto, and stirring is continued for 3 hours after the addition is completed. The obtained mixed solution is placed in a freeze dryer for freeze-drying. After freeze-drying, the obtained solid substance is placed in a muffle furnace and calcined in an air atmosphere to obtain a CuMn-1 catalyst, and the copper-manganese metal molar ratio is 1:1.

[0010] Preferably, the copper-manganese spinel catalyst quartz sand is mixed evenly and poured into a reaction tube, the reaction tube is placed in a fixed bed reactor, anhydrous ethanol is pumped into a preheater by a micro-injection pump for gasification and mixed with the introduced gas N2 before entering the reaction bed, at 280°C, atmospheric pressure, and a mass space velocity of 31.72h-1 Under the conditions, the reaction produces acetaldehyde and hydrogen.

[0011] Preferably, 2416 mg Cu(NO3)2.3H2O, 2450 mg Mn(CH3COO)2.4H2O and 3846.9 mg citric acid are dissolved in 30 mL of deionized water, stirred and mixed evenly, 20 mL of anhydrous ethanol is added dropwise thereto, and stirring is continued for 3 h after the addition is completed, and the obtained mixed solution is placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid substance is placed in a muffle furnace, calcined at 500°C for 4 h in an air atmosphere, cooled to room temperature, taken out, and ground for use, which is a CuMn-1 catalyst;

[0012] 100 mg of CuMn-1 catalyst was mixed with 400 mg of quartz sand and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h-1, and the mass space velocity was 31.72 h-1. The reaction was carried out at 280°C and normal pressure.

[0013] Preferably, Cu(NO3)2.3H2O, Mn(NO3)2.4H2O and citric acid are dissolved in ethanol and deionized water to form a mixed solution, the mixed solution is stirred at 60°C for 1 hour, stirred at 90°C to obtain a wet gel, the wet gel is dried in an oven at 100°C for 12 hours to obtain a dry gel, and the dry gel is calcined in a muffle furnace under an air atmosphere to obtain a CuMn-2 catalyst.

[0014] Preferably, Cu(NO3)2.3H2O, Mn(NO3)2.4H2O and citric acid are dissolved in deionized water to obtain a mixed solution, aqueous ammonia is added dropwise to adjust the pH value to 6-7, the mixed solution is continuously stirred in a 90°C water bath to obtain a wet gel, the wet gel is dried at 110°C for 12 hours to obtain a dry gel, and the dry gel is calcined in a muffle furnace under an air atmosphere to obtain a CuMn-3 catalyst.

[0015] Preferably, Cu(NO3)2.3H2O and Mn(NO3)2.4H2O are dissolved in deionized water, recorded as solution A, NaOH and Na2CO3 are dissolved in deionized water, recorded as solution B, A is placed in a 65°C oil bath, solution B is added dropwise to solution A, stirred for 12 hours, naturally cooled to room temperature, taken out, and filtered until the solution is neutral, the solid substance is dried at 100°C for 12 hours, ground and placed in a muffle furnace, and calcined in an air atmosphere to obtain a CuMn-4 catalyst.

[0016] Preferably, the copper-manganese spinel catalyst is calcined at 400-500° C. in an air atmosphere.

[0017] The invention provides a catalyst for preparing acetaldehyde by direct dehydrogenation of ethanol, which comprises active components Cu and Mn and a chelating agent, wherein the molar ratio of the active components Cu and Mn is (2-1): (1-2).

[0018] The molar ratio of the active components Cu and Mn is selected from one of 1:1, 1:2 and 2:1.

[0019] The molar ratio of the active components Cu and Mn is 1:1.

[0020] The molar ratio of the active components copper and manganese to the chelating agent is 1:1.

[0021] The present invention also provides a method for preparing acetaldehyde by direct dehydrogenation of ethanol. Under the conditions of reaction temperature of 160-280°C and normal pressure, ethanol is injected into a reactor carrying the above catalyst to directly dehydrogenate and produce acetaldehyde and hydrogen.

[0022] Beneficial effects:

[0023] (1) Compared with general oxides and composite oxides, the copper-manganese spinel structure in the present application is a face-centered cubic structure, in which oxygen ions are closely packed in a face-centered cubic structure, copper ions fill 1 / 8 of the tetrahedral centers, and manganese ions fill 1 / 2 of the octahedral centers. The [MnO6] octahedral layers are alternately arranged with the co-layers of [CuO4] tetrahedrons and [MnO6] octahedrons, giving it a unique catalytic activation ability. By regulating the copper-manganese ratio in the copper-manganese spinel, catalytic active sites that are helpful for the anaerobic dehydrogenation of ethanol to produce acetaldehyde and hydrogen are further obtained.

[0024] (2) The mass space velocity of the copper-manganese spinel catalyst in the system is (31.72h -1 ) is higher than the reported value, which solves the problem of low catalyst mass space velocity in the reaction system of ethanol dehydrogenation to acetaldehyde, achieves high catalytic activity under high mass space velocity conditions, and also achieves the goals of high product space-time yield and high atomic utilization rate, and has broad prospects for industrial application.

[0025] (3) When other experimental conditions were the same, the ethanol conversion rate increased significantly with the increase of reaction temperature, from 8.7% at 160°C to 71% at 280°C. However, the acetaldehyde selectivity decreased slightly, but remained above 95% overall. Later, we decided to use 280°C for long-term stability testing. Figure 1 We can see that the CuMn-1 catalyst has a mass space velocity of 31.72 h -1 , under 280°C conditions, the catalyst showed no obvious deactivation after 80 cycles (ie, Example 1).

[0026] (4) At 160°C, the flow rate of anhydrous ethanol is 0.54 mL·h -1 , mass airspeed is 2.84h -1 , the reaction is carried out under normal pressure conditions, the ethanol conversion rate can reach 88.5%, and the acetaldehyde selectivity can reach 99% (i.e., Example 9).

[0027] (5) Increasing the mass of the catalyst and reducing the mass space velocity of ethanol have a certain effect on the conversion rate and selectivity of ethanol. The mass space velocity is reduced from 28.83h -1 (i.e. Example 11) increased to 37.32h -1 (i.e., Example 10), the ethanol conversion rate changed from 84.3% to 69.4%, the acetaldehyde selectivity changed from 93.3% to 93.7%, and the mass space velocity was 31.72h -1 Under these conditions, the ethanol conversion rate was 71% and the acetaldehyde selectivity was about 95%. In the later stage, we used a mass space velocity of 31.72h -1 The reaction was carried out under the same conditions (i.e. Example 1).

[0028] (6) The effects of different catalyst preparation methods on the reaction system were explored. The coprecipitation method, sol-gel method, ammonia pH adjustment sol-gel method, and freeze-assisted sol-gel method were explored respectively. The ethanol conversion rates of the first three catalyst preparation methods were lower than those of the freeze-assisted sol-gel method. Figure 2 It can be seen that the crystal structure of the catalysts prepared by the first three preparation methods is not as good as that of the catalyst prepared by the cryo-assisted sol-gel method, so we finally adopted the cryo-assisted sol-gel method to prepare the catalyst (ie, Example 1).

[0029] (7) Exploring the effect of different copper-manganese metal molar ratios on the reaction system, we explored the copper:manganese (molar ratio) = 1:1

[0030] (CuMn-1), 1:2 (CuMn-5) and 2:1 (CuMn-6). Compared with the catalyst with a copper-manganese molar ratio of 1:1, the catalytic performance of the other two metal molar ratios is slightly lower. It is speculated that this is related to the number of metal active sites. Therefore, we finally used the cryo-assisted sol-gel method to prepare a catalyst with a copper-manganese molar ratio of 1:1 (ie, Example 1).

[0031] (8) The effects of different copper-manganese metal source catalysts on the reaction system were explored. Manganese acetate tetrahydrate and manganese nitrate tetrahydrate were explored as manganese metal sources. The catalytic performance of the two manganese metal source catalysts in the reaction system was not much different. However, XRD characterization showed that Figure 4 We can see that when manganese acetate tetrahydrate is used as the manganese metal source, the catalyst crystal structure is better (ie, Example 1). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1The cyclic stability diagram of CuMn-1 catalyst

[0033] Figure 2 This is the XRD pattern of copper manganese spinel catalyst

[0034] Figure 3 The catalytic performance diagram of catalysts with different metal molar ratios

[0035] Figure 4 XRD patterns of catalysts with different manganese metal sources DETAILED DESCRIPTION

[0036] The present invention is further described below by means of specific examples, but the following examples do not limit the scope of protection claimed in the present invention.

[0037] Example 1

[0038] The copper-manganese spinel catalyst was prepared by a freezing-assisted sol-gel method. The specific operation is as follows: 2416 mg Cu(NO3)2.3H2O, 2450 mg Mn(CH3COO)2.4H2O and 3846.9 mg citric acid were dissolved in 30 mL of deionized water, stirred and mixed evenly, 20 mL of anhydrous ethanol was added dropwise, and stirring was continued for 3 h after the addition was completed. The obtained mixed solution was placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid material was placed in a muffle furnace, calcined at 500 ° C for 4 h in an air atmosphere, cooled to room temperature, taken out, ground for use, and recorded as CuMn-1 catalyst.

[0039] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 1.

[0040] Unless otherwise specified, the flow rate of anhydrous ethanol in the examples is 4.02 mL·h -1 After the reaction is stable, the reaction raw materials and products are analyzed by online chromatography (DB-WAX column, FID detector; Porapak Q column + Colonne Micropacked Shincarbon ST column, TCD detector).

[0041] Example 2

[0042] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 250°C and normal pressure. The reaction results are shown in Table 1.

[0043] Example 3

[0044] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 230°C and normal pressure. The reaction results are shown in Table 1.

[0045] Example 4

[0046] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 210°C and normal pressure. The reaction results are shown in Table 1.

[0047] Example 5

[0048] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 190°C and normal pressure. The reaction results are shown in Table 1.

[0049] Example 6

[0050] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 180°C and normal pressure. The reaction results are shown in Table 1.

[0051] Example 7

[0052] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 170°C and normal pressure. The reaction results are shown in Table 1.

[0053] Example 8

[0054] 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 160°C and normal pressure. The reaction results are shown in Table 1.

[0055] Example 9

[0056] 150 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 0.54 mL·h -1 , mass airspeed is 2.84h -1 , the reaction was carried out at 160°C and normal pressure. The reaction results are shown in Table 1.

[0057] Table 1 Ethanol dehydrogenation performance of CuMn-1 catalyst at different temperatures

[0058]

[0059]

[0060] Summarize:

[0061] Example 9: When the flow rate of anhydrous ethanol is 0.54 mL·h -1 , mass airspeed is 2.84h -1 At 160°C, the ethanol conversion rate was 88.5% and the ethanol selectivity was 99%, indicating that the catalyst can also achieve a relatively good catalytic effect under low temperature conditions. As can be seen from Examples 1-8, when other experimental conditions are the same, with the increase of reaction temperature, the ethanol conversion rate is significantly improved, from 8.7% at 160°C to 71% at 280°C, but the related acetaldehyde selectivity is slightly reduced, but generally maintained above 95%. Later, we decided to use 280°C for long-term stability testing. Figure 1 We can see that the CuMn-1 catalyst has a mass space velocity of 31.72 h -1 Under 280°C conditions, the catalyst showed no obvious deactivation after 80 cycles.

[0062] Note: The cycle steps are: first, introduce anhydrous ethanol for 30 minutes, and analyze the reaction results by online chromatography collection, then turn off the anhydrous ethanol pump, purge with N2 for 30 minutes, introduce air for 30 minutes, turn off the air, purge with N2 for 30 minutes, introduce anhydrous ethanol for 30 minutes, and carry out the cycle reaction in this step.

[0063] *Experimental conditions: reaction temperature 160℃, anhydrous ethanol flow rate 0.54mL·h -1 , catalyst mass 150mg, mass space velocity 2.84h -1 .

[0064] Example 10

[0065] 85 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 37.32h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 2.

[0066] Embodiment 11

[0067] 110 mg CuMn-1 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 28.83h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 2.

[0068] Table 2. Ethanol dehydrogenation performance of CuMn-1 catalyst at different mass space velocities

[0069]

[0070] Summary: Increasing the mass of the catalyst and reducing the mass space velocity of ethanol have a certain effect on the conversion rate and selectivity of ethanol. -1 (i.e. Example 11) increased to 37.32h -1 (i.e., Example 10), the ethanol conversion rate changed from 84.3% to 69.4%, the acetaldehyde selectivity changed from 93.3% to 93.7%, and the mass space velocity was 31.72h -1 Under these conditions, the ethanol conversion rate was 71% and the acetaldehyde selectivity was about 95%. In the later stage, we used a mass space velocity of 31.72h -1 The reaction was carried out under the same conditions (i.e. Example 1).

[0071] Example 12

[0072] Specific preparation method of the catalyst: 966.4 mg Cu(NO3)2.3H2O, 2008 mg Mn(NO3)2.4H2O and 2521.6 mg citric acid are dissolved in ethanol and deionized water to form a mixed solution, the mixed solution is stirred at 60°C for 1 h, stirred at 90°C to obtain a wet gel, the wet gel is dried in an oven at 100°C for 12 h to obtain a dry gel, and the dry gel is calcined in a muffle furnace at 400°C in an air atmosphere for 4 h to obtain a CuMn-2 catalyst.

[0073] 100 mg CuMn-2 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 3.

[0074] Example 13

[0075] The specific preparation method of the catalyst is as follows: 1932.8 mg Cu(NO3)2.3H2O, 4016 mg Mn(NO3)2.4H2O and 3074 mg citric acid are dissolved in deionized water to obtain a mixed solution, ammonia water is added dropwise to adjust the pH value to 6-7, the mixed solution is continuously stirred in a 90°C water bath to obtain a wet gel, the wet gel is dried at 110°C for 12 h to obtain a dry gel, and the dry gel is calcined in a muffle furnace at 400°C in an air atmosphere for 2 h to obtain a CuMn-3 catalyst.

[0076] 100 mg CuMn-3 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 3.

[0077] Embodiment 14

[0078] Specific preparation method of the catalyst: 1932.8 mg Cu(NO3)2.3H2O and 4016 mg Mn(NO3)2.4H2O were dissolved in deionized water, recorded as solution A, 640 mg NaOH and 1696 mg Na2CO3 were dissolved in deionized water, recorded as solution B, A was placed in a 65°C oil bath, solution B was added dropwise to solution A, stirred for 12 hours, naturally cooled to room temperature, taken out, filtered until the solution was neutral, the solid material was dried at 100°C for 12 hours, ground and placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours to obtain CuMn-4 catalyst.

[0079] 100 mg of CuMn-1 and CuMn-4 catalysts were mixed with 400 mg of quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 3.

[0080] Table 3. Ethanol dehydrogenation performance of catalysts prepared by different methods

[0081]

[0082] Summary: The effects of different catalyst preparation methods on the reaction system were explored, including coprecipitation method, sol-gel method, ammonia pH adjustment sol-gel method and freezing-assisted sol-gel method. The ethanol conversion rates of the first three catalyst preparation methods were lower than those of the freezing-assisted sol-gel method. Figure 2 It can be seen that the crystal structure of the catalysts prepared by the first three preparation methods is not as good as that of the catalyst prepared by the cryo-assisted sol-gel method, so we finally adopted the cryo-assisted sol-gel method (Example 1) to prepare the catalyst.

[0083] Embodiment 15

[0084] The copper-manganese spinel catalyst was prepared by a freezing-assisted sol-gel method. The specific operation is as follows: 2416 mg Cu(NO3)2.3H2O, 4901.8 mg Mn(CH3COO)2.4H2O and 3846.9 mg citric acid were dissolved in 30 mL of deionized water, stirred and mixed evenly, 20 mL of anhydrous ethanol was added dropwise, and stirring was continued for 3 h after the addition was completed. The obtained mixed solution was placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid material was placed in a muffle furnace, calcined at 500°C for 4 h in an air atmosphere, cooled to room temperature, taken out, ground for use, and recorded as CuMn-5 catalyst.

[0085] 100 mg CuMn-5 catalyst was mixed with 400 mg quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 4.

[0086] Example 16

[0087] The copper-manganese spinel catalyst was prepared by a freezing-assisted sol-gel method. The specific operation is as follows: 1997.7 mg Cu(NO3)2.3H2O, 980.35 mg Mn(CH3COO)2.4H2O and 2305.4 mg citric acid were dissolved in 30 mL of deionized water, stirred and mixed evenly, 20 mL of anhydrous ethanol was added dropwise, and stirring was continued for 3 h after the addition was completed. The obtained mixed solution was placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid material was placed in a muffle furnace, calcined at 500°C for 4 h in an air atmosphere, cooled to room temperature, taken out, ground for use, and recorded as CuMn-6 catalyst.

[0088] 100 mg of CuMn-1 and CuMn-6 catalysts were mixed with 400 mg of quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 , the reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 4.

[0089] Table 4. Ethanol dehydrogenation performance of catalysts with different metal molar ratios

[0090]

[0091] Summary: We explored the effect of different copper-manganese metal molar ratios on the reaction system, and explored copper: manganese (molar ratio) = 1:1 (CuMn-1), 1:2 (CuMn-5) and 2:1 (CuMn-6). Compared with the catalyst with a copper-manganese molar ratio of 1:1, the catalytic performance of the other two metal molar ratios was slightly lower. We speculate that this is related to the number of metal active sites, so we finally used the cryo-assisted sol-gel method to prepare a copper-manganese molar ratio of 1:1 catalyst.

[0092] Embodiment 17

[0093] The copper-manganese spinel catalyst was prepared by a freezing-assisted sol-gel method. The specific operation is as follows: 1932.8 mg Cu(NO3)2.3H2O, 4016 mg Mn(NO3)2.4H2O and 3074 mg citric acid were dissolved in 30 mL of deionized water, stirred and mixed evenly, 20 mL of anhydrous ethanol was added dropwise, and stirring was continued for 3 h after the addition was completed. The obtained mixed solution was placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid material was placed in a muffle furnace, calcined at 500°C for 4 h in an air atmosphere, cooled to room temperature, taken out, ground and used, and recorded as CuMn-7 catalyst.

[0094] 100 mg of CuMn-1 and CuMn-7 catalysts were mixed with 400 mg of quartz sand (30-40 mesh) and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass airspeed is 31.72h -1 The reaction was carried out at 280°C and normal pressure. The reaction results are shown in Table 5.

[0095] Table 5. Ethanol dehydrogenation performance of different metal source catalysts

[0096]

[0097] Summary: To explore the effect of different copper-manganese metal source catalysts on the reaction system, manganese acetate tetrahydrate and manganese nitrate tetrahydrate were explored as manganese metal sources. The catalytic performance of the two manganese metal source catalysts in the reaction system was not much different, but the XRD characterization showed that Figure 4 We can see that when manganese acetate tetrahydrate is used as the manganese metal source, the catalyst crystal structure is better.

[0098] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. An application of a copper-manganese spinel catalyst in the dehydrogenation of ethanol to prepare acetaldehyde, characterized in that: 2416 mg Cu(NO3)2.3H2O, 2450 mg Mn(CH3COO)2.4H2O and 3846.9 mg citric acid were dissolved in 30 mL deionized water, stirred and mixed evenly, 20 mL anhydrous ethanol was added dropwise thereto, and stirring was continued for 3 h after the addition was completed. The obtained mixed solution was placed in a freeze dryer for freeze drying. After freeze drying, the obtained solid material was placed in a muffle furnace, calcined at 500 °C for 4 h in an air atmosphere, cooled to room temperature, taken out, ground and used as a CuMn-1 catalyst; 100 mg CuMn-1 catalyst was mixed with 400 mg quartz sand and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass space velocity is 31.72 h -1 , the reaction was carried out at 280 °C and normal pressure.

2. Application of a copper-manganese spinel catalyst in the dehydrogenation of ethanol to produce acetaldehyde, characterized in that: 966.4 mg Cu(NO3)2.3H2O, 2008 mg Mn(NO3)2.4H2O and 2521.6 mg citric acid were dissolved in ethanol and deionized water to form a mixed solution. The mixed solution was stirred at 60 °C for 1 h and stirred at 90 °C to obtain a wet gel. The wet gel was dried in an oven at 100 °C for 12 h to obtain a dry gel. The dry gel was calcined in a muffle furnace at 400 °C in air atmosphere for 4 h to obtain the CuMn-2 catalyst; 100 mg CuMn-2 catalyst was mixed with 400 mg 30-40 mesh quartz sand and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass space velocity is 31.72 h -1 , the reaction was carried out at 280°C and normal pressure.

3. Application of a copper-manganese spinel catalyst in the dehydrogenation of ethanol to produce acetaldehyde, characterized in that: 1932.8 mg Cu(NO3)2.3H2O, 4016 mg Mn(NO3)2.4H2O and 3074 mg citric acid were dissolved in deionized water to obtain a mixed solution, and ammonia water was added dropwise to adjust the pH value to 6-7. The mixed solution was stirred continuously in a 90 ℃ water bath to obtain a wet gel, and the wet gel was dried at 110 ℃ for 12 h to obtain a dry gel, and the dry gel was calcined in a muffle furnace at 400 ℃ in air atmosphere for 2 h to obtain a CuMn-3 catalyst; 100 mg CuMn-3 catalyst was mixed with 400 mg 30-40 mesh quartz sand and loaded into a fixed bed reaction tube, which was placed in a fixed bed reactor. Anhydrous ethanol was pumped into the preheater of the fixed bed reactor through a micro-injection pump for preheating, and then mixed with the introduced gas N2 and entered the reaction bed. The flow rate of anhydrous ethanol was 4.02 mL·h -1 , mass space velocity is 31.72 h -1 , the reaction was carried out at 280°C and normal pressure.

Citation Information

Patent Citations

  • Catalyst for preparing acetaldehyde by ethanol dehydrogenation and its preparation method and use

    CN105148911A

  • Catalyst for direct dehydrogenation preparation of ethanol to acetaldehyde and preparation method and application of catalyst

    CN110385139A

  • Catalyst for preparing acetaldehyde through ethanol dehydrogenation and preparation method thereof

    CN110479337A

  • Oxygen defect-enriched spinel type metal oxide / graphene composite electrode material and preparation method thereof

    CN110534346A

  • Spinel catalyst as well as preparation method and application thereof

    CN115245820A